Advancing Stewardship and Civil Service Acumen through Scholarly Dissemination - Eogenie Lakilaki; Edi Wiyono; Arief Budiman; Haryo Nurtiar; Sumitro Sumitro (Information Technology and Science (ITScience), 2026)
This study explores the substantive impact of a scientific publication dissemination programme conducted at the Bureau of Planning and Finance of the National Library of the Republic of Indonesia (Perpusnas). The programme was conceived to reinforce governance coherence while advancing the intellectual and professional acumen of State Civil Apparatus (ASN) through systematic training in academic writing and scholarly publication. At its core, the initiative seeks to reconcile administrative practice with evidence-informed policymaking by equipping ASNs with the analytical, methodological, and ethical proficiencies required for peer-reviewed academic production. The programme is underpinned by a Hexahelix collaborative framework, encompassing academia, government, professional bodies, civil society, media, and industry, complemented by an emphasis on data literacy and rigorous scientific discipline. This integrative approach enables ASNs to engage more substantively in informed public deliberation, thereby contributing to enhanced transparency, accountability, and institutional legitimacy within public governance structures. The findings reveal a marked improvement in participants’ scholarly capability, with 92.85 per cent demonstrating sustained motivation to pursue further publication endeavours. Moreover, five ASNs succeeded in publishing articles in SINTA 4-accredited journals. In sum, the programme represents a strategic advancement in aligning civil service competencies with national development imperatives, while simultaneously cultivating a resilient culture of knowledge exchange, reflective practice, and continuous professional development across the public sector.